Tuning the optical properties of the metal–organic framework UiO-66 via ligand functionalization. Issue 8 (13th February 2023) - Treger, Marvin; Hannebauer, Adrian; Schaate, Andreas; Budde, Jan L.; Behrens, Peter; Schneider, Andreas M.
Abstract : Metal–organic frameworks (MOFs) possess a modular construction. By varying the functional groups on the linker unit, the refractive index n of UiO-66 MOFs can be tuned over a wide range, as high-level band structure calculations show. Abstract : Metal–organic frameworks (MOFs) are a promising class of materials for optical applications, especially due to their modular design which allows fine-tuning of the relevant properties. The present theoretical study examines the Zr-based UiO-66-MOF and derivatives of it with respect to their optical properties. Starting from the well-known monofunctional amino- and nitro-functionalized UiO-66 derivatives, we introduce novel UiO-66-type MOFs containing bifunctional push–pull 1, 4-benzenedicarboxylate ( bdc ) linkers. The successful synthesis of such a novel UiO-66 derivative is also reported. It was carried out using a para -nitroaniline (PNA)-based bdc -analogue linker. Applying density functional theory (DFT), suitable models for all UiO-66-MOF analogues were generated by assessing different exchange–correlation functionals. Afterwards, HSE06 hybrid functional calculations were performed to obtain the electronic structures and optical properties. The detailed HSE06 electronic structure calculations were validated with UV-Vis measurements to ensure reliable results. Finally, the refractive index dispersion of the seven UiO-66-type materials is compared, showing the possibility to tailor the optical properties by the use of functionalized linker molecules. Specifically, the refractive index can be varied over a wide range from 1.37 to 1.78.